2000
DOI: 10.4049/jimmunol.164.2.893
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Characterization of Phenotypic Ig Heavy Chain Allelically Included IgM-Expressing B Cells in Mice

Abstract: Ig H chain (IgH) allelic exclusion remains a puzzling topic. Here, we address the following question: Do phenotypic IgH allelically included cells exist in normal mice and, if so, at what frequency? Sorted cells from heterozygous mice were evaluated for the expression of both IgM allotypes by double intracytoplasmic stainings. Dual expressors were found at a frequency of 1 in 104 splenic B cells. These data were confirmed by direct sequencing of IgH-rearranged alleles obtained after single cell (or clone) PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 32 publications
(34 reference statements)
2
40
0
1
Order By: Relevance
“…However, it was shown that the onset of allelic exclusion after successful V H to DJ H recombination is accompanied by the transient downregulation of RAG (Grawunder et al, 1995), decontraction of the IgH locus (Roldán et al, 2005), and loss of accessibility correlates such as V H germline transcripts and marks of active chromatin (see below). It has been estimated that only 1 in 10,000 wild-type Blymphocytes actually escape allelic exclusion and express a functional μHC from both IgH alleles (Barreto and Cumano, 2000). Feedback regulation can explain cessation of V H to DJ H rearrangement but would be ineffective if both IgH alleles would rearrange simultaneously.…”
Section: Igh Rearrangements and Allelic Exclusionmentioning
confidence: 99%
“…However, it was shown that the onset of allelic exclusion after successful V H to DJ H recombination is accompanied by the transient downregulation of RAG (Grawunder et al, 1995), decontraction of the IgH locus (Roldán et al, 2005), and loss of accessibility correlates such as V H germline transcripts and marks of active chromatin (see below). It has been estimated that only 1 in 10,000 wild-type Blymphocytes actually escape allelic exclusion and express a functional μHC from both IgH alleles (Barreto and Cumano, 2000). Feedback regulation can explain cessation of V H to DJ H rearrangement but would be ineffective if both IgH alleles would rearrange simultaneously.…”
Section: Igh Rearrangements and Allelic Exclusionmentioning
confidence: 99%
“…RAG is turned off in B cells expressing a functional, self-tolerant Ig; although perhaps too simplistic, this by and large explains both allelic and isotypic exclusion at the L chain loci. Although it is tempting to propose analogous models for allelic exclusion of IgH and IgL chain genes, there are, in fact, great differences-not only in temporal sequence of gene assembly, but also in strictness of exclusion: a small percentage of B cells does express two different L chains (5), but only one in 10 4 cells expresses two H chains (6).…”
mentioning
confidence: 99%
“…Contrary to the latter prediction, however, only about one in 10 3 -10 4 mature splenic B lymphocytes were found to express two heavy chains in the cytoplasm (23,44). The same level of allelic exclusion was found even in mice triallelic for the Ig heavy chain locus (9).…”
Section: Heavy Chainmentioning
confidence: 55%